2013
DOI: 10.1523/jneurosci.0079-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Inhibition Reduces Information Redundancy at Presentation of Communication Sounds in the Primary Auditory Cortex

Abstract: In all sensory modalities, intracortical inhibition shapes the functional properties of cortical neurons but also influences the responses to natural stimuli. Studies performed in various species have revealed that auditory cortex neurons respond to conspecific vocalizations by temporal spike patterns displaying a high trial-to-trial reliability, which might result from precise timing between excitation and inhibition. Studying the guinea pig auditory cortex, we show that partial blockage of GABA A receptors b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(99 citation statements)
references
References 87 publications
4
93
2
Order By: Relevance
“…In contrast, we did not observe the increase of spike timing reliability reported in Gaucher et al (2013). This may indicate different processing strategies between the IC and auditory cortex, but it may also be a consequence of the different pharmacological protocols.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, we did not observe the increase of spike timing reliability reported in Gaucher et al (2013). This may indicate different processing strategies between the IC and auditory cortex, but it may also be a consequence of the different pharmacological protocols.…”
Section: Discussioncontrasting
confidence: 99%
“…These could then be processed by intrinsic circuits in the cortex, involving inhibition of selected elements (Gaucher et al, 2013a), or convergence of different thalamic inputs in order to produce a much greater range of cortical response combinations. Some of our orthogonal tracks were consistent with the idea of convergence from different thalamic inputs and inhibition is undoubtedly involved, but overall the variety of chutter response combinations identified in the thalamus appeared to be just as great as in the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…This theory is based on the expectation that there is a relatively small degree of redundancy within cortical responses and so finding large numbers of identical responses to a call sequence would be inconsistent with this view. Recent work has shown that at the level of individual neurons there is relatively little redundancy in the response to conspecific calls such as chutter partly as a result of local inhibition within AI (Gaucher et al, 2013a). Our results were consistent with other work showing that the temporal sparse code found in AI is a first step in generating a high level representation of conspecific vocalizations (Gaucher et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Since the three tested vocalizations had different lengths (from 90 ms for the “chirp,” up to 1740 ms for the “chutter”), only the first 90 ms were analyzed to allow pooling of the responses to different vocalizations. The spike timing reliability was computed using the CorrCoef as in previous studies (Gaucher et al, 2013a). It corresponds to the normalized covariance between each pair of spike trains recorded at presentation of this vocalization and was calculated as follows: CorrCoef=1N(N1)i=1N1j=i+1Nσxixjσxiσxj where N is the number of trials and σ x i x j is the normalized covariance at zero lag between spike trains x i and x j where i and j are the trial numbers.…”
Section: Methodsmentioning
confidence: 99%